2020
DOI: 10.1002/bdm.2167
|View full text |Cite
|
Sign up to set email alerts
|

Reasons or rationalizations: The role of principles in the moral dumbfounding paradigm

Abstract: Moral dumbfounding occurs when people maintain a moral judgment even though they cannot provide reasons for it. Recently, questions have been raised about whether dumbfounding is a real phenomenon. Two reasons have been proposed as guiding the judgments of dumbfounded participants: harm‐based reasons (believing an action may cause harm) or norm‐based reasons (breaking a moral norm is inherently wrong). Participants in that research (see Royzman, Kim, & Leeman, 2015), who endorsed either reason were excluded fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…However, more recent dumbfounding work fails to support the TDM perspective on this matter ( McHugh et al, 2020 ). In addressing specific methodological limitations of the Royzman et al (2015) study, McHugh et al (2020) found that people do not consistently cite harm as a reason for their judgment.…”
Section: Examining the Explanatory Power Of Mjacmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more recent dumbfounding work fails to support the TDM perspective on this matter ( McHugh et al, 2020 ). In addressing specific methodological limitations of the Royzman et al (2015) study, McHugh et al (2020) found that people do not consistently cite harm as a reason for their judgment.…”
Section: Examining the Explanatory Power Of Mjacmentioning
confidence: 99%
“…However, more recent dumbfounding work fails to support the TDM perspective on this matter ( McHugh et al, 2020 ). In addressing specific methodological limitations of the Royzman et al (2015) study, McHugh et al (2020) found that people do not consistently cite harm as a reason for their judgment. Participants were asked to judge a vignette describing consensual incest, asked to provide reasons for their judgment, and then provided with the questions examining perceptions of harm developed by Royzman et al The responses to the harm-based questions provided one measure of participants’ perceptions of harm, that is, whether participants endorsed a harm-based reason for their judgment when it was presented to them.…”
Section: Examining the Explanatory Power Of Mjacmentioning
confidence: 99%
See 1 more Smart Citation
“…Causing harm to another person is relatively consistently categorized as MORALLY WRONG (Cushman et al, 2012;Schein & Gray, 2018; though not with perfect consistency, e.g., Alicke, 2012;McHugh et al, 2020). This relative consistency means that encountering an event in which harm is caused by the actions of an agent is highly likely to be categorized as MORALLY WRONG.…”
Section: Patmentioning
confidence: 99%
“…point to a series of studies byRoyzman et al (2015), to support their appeal to perceived harm in the "moral dumbfounding" paradigm Royzman et al (2015). investigating the case of consensual incest, included additional questions that appear to demonstrate that people's judgments were (at least in part) grounded in perceptions of harm.However, more recent work on dumbfounding fails to support the TDM perspective on this matter(McHugh et al, 2020). In addressing specific methodological limitations of theRoyzman et al (2015) study, McHugh et al (2020 found that people do not cite harm as a reason for their judgment.…”
mentioning
confidence: 99%